Pelatihan Public Speaking Dasar Untuk Siswa Sekolah Dasar Islam Fastabiqul Khairot Pada Kelas Tinggi - Syamzaimar, Syamzaimar; Hayani , Surma (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2025)
Public speaking is an essential skill that should be developed from an early age to foster students’ confidence and communication abilities. Initial observations at SD Islam Fastabiqul Khairot revealed that many upper-grade students experienced anxiety and a lack of self-confidence when speaking in public. To address this issue, this community service program was implemented in the form of basic public speaking training using the Participatory Action Research (PAR) approach. The training consisted of eight sessions and involved 11 students from grades IV, utilizing interactive methods such as role-play, storytelling, and group presentations. The results of the pre-test and post-test showed significant improvement: the number of students in the low-confidence category decreased from 7 to 1, while those in the high and very high categories increased from 1 to 6 students. Student participation also improved, with 72.8% categorized as active or highly active during the sessions. This program proved effective in enhancing students’ communication skills and encouraging them to speak confidently in public. Therefore, the basic public speaking training is recommended for continued implementation and expansion to other education levels